Obstetrices y medicae: la resiliencia femenina en la medicina romana (Tema Central) - Barreiro Morales, María Elisabet (2026)
This paper analyzes the role of women in medicine in Ancient Rome within a deeply patriarchal legal and social system. Although women were legally subordinated to male figures through institutions such as the tutela mulierum, they managed to play key roles in the medical field, particularly in gynecology and obstetrics. Obstetrices (midwives), often slaves or freedwomen, assisted in childbirth, managed contraceptive methods, and participated in legal proceedings related to reproduction. On the other hand, medicae, generally free women, held a higher social status and were able to treat various illnesses, even acting as general practitioners. Furthermore, this article highlights the lack of public hospitals in Rome, which meant that medical practice was mainly carried out in private spaces such as homes or small street clinics. While there was an official medicine influenced by Greek tradition, an empirical, popular medicine persisted, transmitted orally by women. Despite legal restrictions and the lack of formal recognition, women developed valuable and functional medical knowledge, especially concerning women’s health. The legacy of these healers is a testament to their resilience and adaptability in an environment that, although restrictive, could not do without their knowledge and work. Their role was essential in ensuring the continuity of community health in Rome.